2000
DOI: 10.1007/s002610000058
|View full text |Cite
|
Sign up to set email alerts
|

Atypical exocrine and endocrine pancreatic tumors (anaplastic, small cell, and giant cell types): CT and pathologic features in 14 patients

Abstract: Although a specific diagnosis may not be possible in some cases, we believe that knowledge of certain pathologic and computed tomographic features should lead to optimal diagnosis, therapy, and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 0 publications
2
47
1
1
Order By: Relevance
“…PNEN shows varied enhancement on dynamic CT. [17][18][19][20][21]30 As shown in Figure 1A, tumors with typical findings are easy to diagnose, but some neoplasms cannot be differentiated from pancreatic adenocarcinomas. 31 Therefore, the diagnostic accuracy of dynamic CT is insufficient, with 64-81% of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNEN shows varied enhancement on dynamic CT. [17][18][19][20][21]30 As shown in Figure 1A, tumors with typical findings are easy to diagnose, but some neoplasms cannot be differentiated from pancreatic adenocarcinomas. 31 Therefore, the diagnostic accuracy of dynamic CT is insufficient, with 64-81% of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Inversely, it is reported that characteristic finding of small cell cancer of pancreas takes on a slight enhanced effect with CT using contrast agent. 21 However, there is no detailed report about the correlation between pathological grade based on WHO2010 and quantitative evaluation of the enhancement on enhanced CT.…”
Section: X190mm (96 X 96 Dpi)mentioning
confidence: 99%
“…CT depicts this neoplasm as large thick-walled cystic masses with a ragged inner contour, due to central hemorrhagic necrosis. Otherwise, solid masses with a relatively low attenuation center are found [10][11]. No distinctive CT features that allow the differentiation from ductal adenocarcinoma have been reported.…”
Section: Pleomorphic Giant Cell Carcinomamentioning
confidence: 99%
“…Undifferentiated carcinoma of the pancreas is a rare and aggressive tumor; accounts for 2-7% of all pancreatic cancers (1)(2)(3)(4). The prognosis of undifferentiated carcinoma of the pancreas is worse than that of poorly differentiated ductal adenocarcinoma of the pancreas (5).…”
Section: Introductionmentioning
confidence: 99%